Post-covid Tourist Satisfaction in the Hospitality industry: Reflections from Jordan - Bader, Malek; Al Rousan, Ramzi; Khasawneh, Nermin; Niyas KK, Mohammed (Technium Social Sciences Journal, 2023)
This study sets out to investigate the effects of COVID-19 on the tourism industry in Jordan by studying the satisfaction of tourists after the lockdown. This study focuses on three main areas that may influence tourists' satisfaction. The tourist satisfaction study was conducted using a questionnaire designed and distributed among tourists who used the services. Other than that, all the tourist guides from the six travel agencies involved in this study were interviewed for cross-checking purposes. There was a shift in the satisfaction level after the pandemic's peak. The three main areas that determine satisfaction are services provided by travel agencies, facilities for tourists at their destinations, and accommodations. The findings suggested the tourists demanded proper COVID-19 standard operating procedures in addition to the basic requirements of the services provided. Data will inform stakeholders on the preparation of services provided for the post-COVID-19 tourism industry.